2001
DOI: 10.1210/jcem.86.11.7998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leptin in Human Saliva

Abstract: Leptin is produced predominantly in adipose tissue but has recently also been found in gastric mucosa. It has been shown that the oral application of leptin induces neuronal activity in the brain stem of rodents. The objective of the present study was to identify this hormone in human saliva and to examine the production and stability of salivary leptin. We have demonstrated production of leptin in salivary glands and oral mucosa by RT-PCR, its storage by immunocytochemistry, and the release of the peptide by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 29 publications
4
69
0
6
Order By: Relevance
“…Recently we demonstrated the expression of leptin by the human salivary glands (Gröschl et al 2001). Other authors have shown a direct atrophic effect of leptin on the salivary glands of rats (Higa et al 2002).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recently we demonstrated the expression of leptin by the human salivary glands (Gröschl et al 2001). Other authors have shown a direct atrophic effect of leptin on the salivary glands of rats (Higa et al 2002).…”
Section: Introductionmentioning
confidence: 81%
“…The recent discovery of both leptin and leptin receptors in the stomach (Bado et al 1998, Cinti et al 2000 and the presence of leptin in saliva (Gröschl et al 2001) has led to further questions about peripheral leptin actions, which may influence food uptake, digestion or mucosal proliferation in a still unknown manner.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12]16 This study sought to assess the concentration differences of leptin in saliva between normal weight and overweight individuals and its correlation with orthodontic tooth movement. An association was found in this study between salivary leptin levels, BMI, and orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Leptin is a 16-KDa, nonglycosylated polypeptide hormone produced primarily by adipocytes and in minor quantities by the placenta, stomach, osteoblast, and salivary glands. [7][8][9][10][11][12] There is a strong positive correlation between serum leptin concentration and body mass index (BMI) or fat mass. [13][14][15] Leptin plays a dual role as a hormone and cytokine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation